INNOVATION OF DIFFERENTIATIONAL LEARNING STRATEGIES IN SCIENCE LEARNING FOR STUDENTS WITH SPECIAL NEEDS - Amin, Lailla Hidayatul; Na'imah, Na'imah; Dewanti, Sintha Sih; Delimanugari, Daluti; Suprihatiningrum, Jamil; Trisnawati, Septian Nur Ika; Maulida, Chusna (PD PGMI se Indonesia, 2024)
This study was conducted to explore the application of differentiation learning strategies and inclusive approaches for students with special needs in Elementary Schools. This study is motivated by the importance of creating a friendly learning environment and supporting the development of students with special needs so that they can develop according to their potential. The research method used is a qualitative study with a phenomenological approach, where data was obtained through in-depth interviews with three key informants, namely educators and inclusive program managers at schools. The data collected were analyzed thematically to identify patterns of implementation of differentiation learning strategies and implementation of inclusive policies. The results of the study indicate that (1) Teachers have implemented differentiation learning strategies optimally, learning methods and materials are adjusted to the needs and competencies of students with special needs; (2) Special programs; Maintenance Class and Inclusive Learning are applied to provide additional support for students, including the use of special aids and accompanying teachers; (3) The humanist philosophy approach is also the basis for creating an inclusive learning environment, which is demonstrated through respect for individual uniqueness and student character development. Evaluation of this approach is carried out periodically to ensure its suitability to student needs. In addition, collaboration with parents and the community is considered very important in supporting the implementation of inclusive programs.